The Logic of Excess - Simons, Peter (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
Statements such as ‘This house is too expensive for me to buy’, ‘Jim is old enough to join the Navy’, and similar and related statements, have to do with excess and sufficiency. They are connected in meaning systematically enough to sustain their own local logic. The chief difficulty in formulating this logic is that of discerning the best way to represent such statements and to take account of the loose fit between a strict logic and ordinary ways of speaking about excess and its cognates. This paper examines this hitherto virtually unexplored area, providing examples, analysis, axioms and models.